SELF-CARE AGENCY IMPROVES PERSONAL HYGIENE OF ELDERLY IN A NURSING HOME IN BINJAI [SELF-CARE AGENCY MENINGKATKAN PERSONAL HYGIENE PADA LANSIA DI PANTI WERDA BINJAI] - Lindawati Simorangkir; Endang Sinaga (Nursing Current: Jurnal Keperawatan, 2019)
The Self-Care Agency role is to increase knowledge with changing attitudes in driving the elderly to be more aware of the importance of personal hygiene in their daily lives. One attempt in the prevention of disease in the elderly is by doing personal hygiene so that the elderly can better feel comfort, safety and well-being. This study aimed to determine the effect of Self-Care Agency to the personal hygiene of the elderly in nursing home Binjai. The design study is Quasi-Experimental Design Time Series, with the approach of One Group Pre Post Test Design. Sampling was done by purposive sampling with a sample of 30 respondents. Research results pre intervention personal hygiene less category as much as 73%, and post intervention personal hygiene category of "good" as much as 53.3%. Based on the results of the Wilcoxon test showed that the self-care agency signifikat to improving the personal hygiene of the elderly in Panti Werda Binjai, with p value = 0.001. Low personal hygiene of the elderly in nursing home Binjai due to lack of awareness of the importance of self care. It is necessary innovations in providing nursing interventions, assistance, support and cooperation with the nursing home attendant in improving personal hygiene of the elderly.BAHASA INDONESIA Self-Care Agency berperan untuk meningkatkan pengetahuan dengan mengubah sikap dalam mengarahkan lansia untuk lebih menyadari pentingnya melakukan personal hygiene didalam kehidupan sehari-harinya. Salah satu usaha pencegahan penyakit pada lansia dengan melakukan personal hygiene sehingga lansia dapat merasakan kenyamanan, keamanan dan kesejahteraan yang lebih baik. Penelitian ini bertujuan untuk mengetahui pengaruh Self-Care Agency terhadap personal hygiene lansia di Panti Werda Binjai. Desain penelitian yang digunakan Quasi Experimental Time Series Design, dengan pendekatan One Group Pre Post Test Design. Pengambilan sampel dilakukan dengan dengan purposive sampling dengan besar sampel 30 responden. Hasil penelitan pre intervensi personal hygiene kategori kurang sebanyak 73%, dan post intervensi personal hygiene kategori “baik” sebanyak 53,3%. Berdasarkan hasil uji Wilcoxon memperlihatkan bahwa Self-care agency signifikan terhadap peningkatan personal hygiene lansia di Panti Werda Binjai, dengan nilai p value = 0,001. Personal hygiene yang rendah pada lansia di Panti werda Binjai disebabkan kurangnya kesadaran pentingnya perawatan diri. Maka perlu inovasi dalam memberikan intervensi keperawatan, pendampingan, dukungan dan kerjasama dengan petugas panti werda dalam meningkatkan personal hygiene lansia.